Does technology conglomeration promote innovative outcomes of new energy vehicle enterprises? The moderating effect of divisive faultlines. (15th November 2021) - Cheng, Long; Liu, Yihuan; Lou, Xuming; Chen, Zifeng; Yang, Yang
Abstract: Previous research has examined the influence of factors such as technology proximity and relational embeddedness on technological innovation from the perspective of the dyad alliance. However, little is known about the effect of overall technological proximity and overall tie strength distribution on technological innovation in cooperative networks. We use technology conglomeration to represent the technology proximity between individuals and the whole (non-dyad level), and investigate how technology conglomeration affects the innovation outcomes of new energy vehicle enterprises from the perspective of innovation network. Specifically, we introduce divisive faultlines to study the moderating effect of tie strength distribution on the relationship between technology conglomeration and innovation outcomes. Based on Derwent Innovation Index database, we collected 107, 100 new energy vehicle patents applied for from 2004 to 2018, and conducted empirical analysis using fixed effects estimator. We found that technology conglomeration has a significant impact on new energy vehicle enterprises' innovation outcomes. Still, the impact on different types of innovation outcomes is different. Technology conglomeration is positively related to innovation quantity, but this positive correlation tends to weaken when the divisive faultlines is strong. Besides, we find that technology conglomeration is associated with innovation radicalness in an inverted U-shaped relationship. Still, divisive faultlines have no significant moderating effect on this inverted U-shaped relationship. The results also show that divisive faultlines negatively affect the innovation radicalness of enterprises. This finding suggests that for enterprises seeking technological breakthroughs, medium overall technological proximity is an ideal strategy for enterprises to employ. Concurrently, preventing uneven distribution of cooperative tie strength among enterprises is a momentous task for enterprise managers. Highlights: Technology conglomeration has a significant positive impact on innovation quantity of new energy vehicle enterprises. There is a nonlinear relationship between technology conglomeration and innovation radicalness of enterprises. Divisive faultlines weakens this positive relationship between technology conglomeration and innovation quantity. Divisive faultlines has no moderating significant effect on the nonlinear relationship. Divisive faultlines directly has a significant negative impact on innovation radicalness.